Systematic review of innovative ablative therapies for the treatment of locally advanced pancreatic cancer. Issue 3 (18th December 2014) - Rombouts, S. J. E.; Vogel, J. A.; van Santvoort, H. C.; van Lienden, K. P.; van Hillegersberg, R.; Busch, O. R. C.; Besselink, M. G. H.; Molenaar, I. Q.
<x xml:space="preserve">Abstract</x> Background Locally advanced pancreatic cancer (LAPC) is associated with a very poor prognosis. Current palliative (radio)chemotherapy provides only a marginal survival benefit of 2–3 months. Several innovative local ablative therapies have been explored as new treatment options. This systematic review aims to provide an overview of the clinical outcomes of these ablative therapies. Methods A systematic search in PubMed, Embase and the Cochrane Library was performed to identify clinical studies, published before 1 June 2014, involving ablative therapies in LAPC. Outcomes of interest were safety, survival, quality of life and pain. Results After screening 1037 articles, 38 clinical studies involving 1164 patients with LAPC, treated with ablative therapies, were included. These studies concerned radiofrequency ablation (RFA) (7 studies), irreversible electroporation (IRE) (4), stereotactic body radiation therapy (SBRT) (16), high‐intensity focused ultrasound (HIFU) (5), iodine‐125 (2), iodine‐125–cryosurgery (2), photodynamic therapy (1) and microwave ablation (1). All strategies appeared to be feasible and safe. Outcomes for postoperative, procedure‐related morbidity and mortality were reported only for RFA (4–22 and 0–11 per cent respectively), IRE (9–15 and 0–4 per cent) and SBRT (0–25 and 0 per cent). Median survival of up to 25·6, 20·2, 24·0 and 12·6 months was reported for RFA, IRE, SBRT and HIFU respectively. Pain relief was demonstrated for RFA, IRE, SBRT and HIFU. Quality‐of‐life outcomes were reported only for SBRT, and showed promising results. Conclusion Ablative therapies in patients with LAPC appear to be feasible and safe.